Method for Formal Analysis of the Type and Content of Airline Standard Operating Procedures - Bashatah, Jomana; Sherry, Lance (Integrated Communications, Navigation, and Surveillance Conference, 2023)
Standard Operating Procedures (SOPs) are the "glue" that holds complex systems together to ensure a safe and efficient mission. The SOPs define the sequence of navigation procedures and trajectory maneuvers required for normal, abnormal, and emergency operations. SOP Steps define the specific perceptual, cognitive, and physical actions (e.g., button pushes) and communications for each procedure. The type of SOP step (e.g., action-only, decision steps ...) and the clarity and completeness of these written SOPs and their associated steps impact the time to proficiency in training and the mission efficiency and safety.This paper describes a method for analyzing the step type and content of SOPs. The SOP model used to define the step type and content is based on a stimulus-response model of the cognition required to perform each SOP step. A case study analysis of 321 SOP steps for Extravehicular Activities (EVA) for International Space Station (ISS) operations was annotated and analyzed. The SOP steps are classified into four distinct types: Action-only steps (73%), Decision steps (0%), Action with Waiting & Verification (27%), and Decision with Waiting & Verification (0%). SOP Steps with waiting-verification are subject to failure to complete without salient visual cues.The content of the SOP steps showed that the SOP steps require operators to fill in gaps with knowledge regarding the role of each operator, and how to manipulate input devices. For example, the actor in the SOP steps was never included, despite the fact that the procedures were intended to be completed by a couple of operators. Additionally, the motor skill needed to complete the steps was included two percent (2%) of the time, and the input device used was included twelve percent (12%) of the time. The content also took advantage of implicit information. For example, the triggering conditions were included only three percent (3%) of the time. This was mainly due to the sequential nature of the steps, and not needing to be performed once a specific condition has been met. These characteristics significantly impact the time to proficiency in training, and the probability of failure to complete in infrequent operations (e.g. emergency). The implications of these results on training are discussed.